2016
DOI: 10.3390/rs8040304
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Complex Urban Fringe Land Cover Using Evidential Reasoning Based on Fuzzy Rough Set: A Case Study of Wuhan City

Abstract: Urban fringe is the transition zone fine grained with urban and non-urban land cover types. The complex landscape mosaic in this area challenges the land cover classification based on the remote-sensing data. Spectral signatures are not efficient to discriminate all pixels into classes. To improve the recognition and handle the uncertainty, this paper provides a novel integrated approach, based on a fuzzy rough set and evidential reasoning (FRSER), for land cover classification in an urban fringe area. The app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…This ultimately results in a considerable reduction in the open and green areas of that region. Related studies have reported that the increasing level of urbanization was leading to landscape fragmentation in Wuhan [54,55]. This resembles the findings in previous studies [4,5] that the rapid human activity in Dhaka, Bangladesh has leaded to numerous unconnected small patches of vegetation and cultivated land, greater isolation as well as higher percentage of edge areas in patches.…”
Section: Analyses On Urbanization Of Wuhansupporting
confidence: 79%
See 2 more Smart Citations
“…This ultimately results in a considerable reduction in the open and green areas of that region. Related studies have reported that the increasing level of urbanization was leading to landscape fragmentation in Wuhan [54,55]. This resembles the findings in previous studies [4,5] that the rapid human activity in Dhaka, Bangladesh has leaded to numerous unconnected small patches of vegetation and cultivated land, greater isolation as well as higher percentage of edge areas in patches.…”
Section: Analyses On Urbanization Of Wuhansupporting
confidence: 79%
“…This process is similar that which has occurred in Ho Chi Minh [2], Dhaka [1,[3][4][5][6]10], Delhi [7], Hanoi [8] and Ansan [9]. Numerous bare land areas emerging along with urbanization processes have cast irreversible impacts on the urban environment, such as air pollution and soil loss [51][52][53][54][55][56][57]. In the plum rain season, flash flooding hazards have become a serious issue and have caused human death and damages to urban infrastructure in the city [52], similar to that in Dhaka [3].…”
Section: Analyses On Urbanization Of Wuhanmentioning
confidence: 81%
See 1 more Smart Citation
“…It is important to study land use changes in the rural-urban fringe to understand the location of the transition area between urban and non-urban land use types [1,2]. This is also an area with prominent conflicts between farmland protection and urban expansion [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This method reduces classification error compared to Markov random field (MRF)-based contextual classification. Recently, Yang et al [21] proposed a classification approach based on DS theory and fuzzy rough sets. This approach can effectively delineate land cover types in urban fringe areas when uncertainties occur in the processing.…”
Section: Introductionmentioning
confidence: 99%